2016
DOI: 10.2105/ajph.2015.302905
|View full text |Cite
|
Sign up to set email alerts
|

Housing Status, Medical Care, and Health Outcomes Among People Living With HIV/AIDS: A Systematic Review

Abstract: Lack of stable, secure, adequate housing is a significant barrier to consistent and appropriate HIV medical care, access and adherence to antiretroviral medications, sustained viral suppression, and risk of forward transmission. Studies that examined the history of homelessness or problematic housing years before outcome assessment were least likely to find negative outcomes, homelessness being a potentially modifiable contextual factor. Randomized controlled trials and observational studies indicate an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
200
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(217 citation statements)
references
References 174 publications
9
200
2
6
Order By: Relevance
“…Among 152 studies compiled by Aidala et al, 144 showed that housing status was associated with poorer medical care or health outcomes, and 5 studies found that homelessness was associated with an increased risk of premature mortality for PLWHIV [40]. Lieb reported an almost 10-fold increase in the mortality risk (HR = 9.98; 95% CI: 2.34, 42.5) for patients who reported homelessness in the 12 past months, compared to the others [41].…”
Section: Discussionmentioning
confidence: 99%
“…Among 152 studies compiled by Aidala et al, 144 showed that housing status was associated with poorer medical care or health outcomes, and 5 studies found that homelessness was associated with an increased risk of premature mortality for PLWHIV [40]. Lieb reported an almost 10-fold increase in the mortality risk (HR = 9.98; 95% CI: 2.34, 42.5) for patients who reported homelessness in the 12 past months, compared to the others [41].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of stable, secure and adequate housing has been found to be a significant barrier to HIV medical care, access and adherence to ART, sustained viral suppression, as well as transmission risk among people living with HIV. 140 Housing is an important structural barrier to optimal HIV outcomes, for MSM and others living with HIV.…”
Section: Mental Health and Hiv Prevention Engagement And Carementioning
confidence: 99%
“…Data are not widely available for PrEP uptake by PWUD, but one study of 304 PWID in Washington, DC, reported that none of the participants had taken PrEP (Kuo et al, 2016). PWUD meeting clinical guidelines for PrEP may have significant problems with adherence because of factors that define substantial risk, including high levels of substance use, homelessness, depression, and other circumstances and traits that may interfere with daily pill-taking (Aidala et al, 2015). A report from an international PWUD organization described several concerns about PrEP for PWUD, including the feasibility of PrEP; the ethics of PrEP, given suboptimal coverage of the community with ART; and advocacy for PrEP potentially undermining advocacy for harm reduction (Guise, Albers, & Strathdee, 2016; International Network of People who Use Drugs, 2015).…”
Section: Evidence-based Interventions For Pwudmentioning
confidence: 99%